2009
DOI: 10.1073/pnas.0812608106
|View full text |Cite
|
Sign up to set email alerts
|

Genomic–anatomic evidence for distinct functional domains in hippocampal field CA1

Abstract: genetics ͉ genomics ͉ hippocampus ͉ learning and memory ͉ neuroanatomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
272
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 316 publications
(311 citation statements)
references
References 35 publications
29
272
1
4
Order By: Relevance
“…While standard extracellular recording techniques preclude accurate discrimination of these cell subclasses to address possible differential functions, combinations of emerging genetic, optical and in vivo intracellular recording techniques may soon make this possible [105][106][107][108]. This study also determined that gene expression patterns across connected structures were similar [104]; for example the genetic profile of a ventral CA1 neuron was more similar to neurons in the emotional regions of the brain (amygdala, lateral septum, ventral subiculum), than that of a dorsal CA1 neuron.…”
Section: Box 2: Genes In Circuitsmentioning
confidence: 56%
See 1 more Smart Citation
“…While standard extracellular recording techniques preclude accurate discrimination of these cell subclasses to address possible differential functions, combinations of emerging genetic, optical and in vivo intracellular recording techniques may soon make this possible [105][106][107][108]. This study also determined that gene expression patterns across connected structures were similar [104]; for example the genetic profile of a ventral CA1 neuron was more similar to neurons in the emotional regions of the brain (amygdala, lateral septum, ventral subiculum), than that of a dorsal CA1 neuron.…”
Section: Box 2: Genes In Circuitsmentioning
confidence: 56%
“…A recent study [104] suggests that the neurons in the densely-packed superficial pyramidal layer are distinct from the sparser deep layers in dorsal CA1 [104]. While standard extracellular recording techniques preclude accurate discrimination of these cell subclasses to address possible differential functions, combinations of emerging genetic, optical and in vivo intracellular recording techniques may soon make this possible [105][106][107][108].…”
Section: Box 2: Genes In Circuitsmentioning
confidence: 99%
“…Nevertheless, it is clear the HPF has a role in the control of behavior, and in this role it appears to participate, interrelatedly, in mnemonic processes and the processing and integration of multisensory locational ("spatial") and affective ("emotional") information (Hirsh, 1974;Eichenbaum, 2000;Dolan, 2002;Holscher, 2003;Bannerman et al, 2004;Erdi et al, 2005). In addition, recent genetic analysis of Ammon's horn in the mouse has materially increased our understanding of HPF organization (Thompson et al, 2008;Dong et al, 2009;Fanselow and Dong, 2010). With reference to a genome-wide atlas of gene expression in the adult mouse brain (Lein et al, 2007), Dong and colleagues (2009) identified field CA1-expressed genes that delineate several molecularly and spatially distinct populations of field CA1 neurons; moreover, they identified correlations between those field CA1 neuron populations and their also genetically distinct subcortical axonal target regions (Dong et al, 2009); similar findings have been described for field CA3 (Thompson et al, 2008).…”
Section: Cerebral Cortexmentioning
confidence: 99%
“…In addition, recent genetic analysis of Ammon's horn in the mouse has materially increased our understanding of HPF organization (Thompson et al, 2008;Dong et al, 2009;Fanselow and Dong, 2010). With reference to a genome-wide atlas of gene expression in the adult mouse brain (Lein et al, 2007), Dong and colleagues (2009) identified field CA1-expressed genes that delineate several molecularly and spatially distinct populations of field CA1 neurons; moreover, they identified correlations between those field CA1 neuron populations and their also genetically distinct subcortical axonal target regions (Dong et al, 2009); similar findings have been described for field CA3 (Thompson et al, 2008).…”
Section: Cerebral Cortexmentioning
confidence: 99%
See 1 more Smart Citation